Goodbye cruller world - Bolton, Ginger (Bolton, Ginger. Deputy Donut mystery., 2018)
Normally, Emily's eyes tend to glaze over when prospective brides go on about their wedding plans. But when the owner of the clothing shop, Dressed to Kill, asks Emily to design a donut wall for her reception, she's immediately sweet on the idea. With the help of her father-in-law and business partner--the former police chief of Fallingbrook--she hangs the treats from dowels on the wall so guests can help themselves. But that night, when the groom ends up on the floor with signs of poisoning, Emily suspects someone has tampered with her treats. When the groom dies, there's no way to sugarcoat it: she's got a murder on her hands. Despite a list of suspects as long as the guest list, Emily vows to find out who created the killer confection to save her shop's reputation and keep the bride out of handcuffs. She'll have to move fast . . . before the poisoner takes a powder.